2007
DOI: 10.1186/1472-6882-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure for smoking cessation – a pilot study

Abstract: Background: Tobacco smoking is a serious risk to health: several therapies are available to assist those who wish to stop. Smokers who approach publicly funded stop-smoking clinics in the UK are currently offered nicotine replacement therapy (NRT) or bupropion, and group behaviour therapy, for which there is evidence of effectiveness. Acupuncture and acupressure are also used to help smokers, though a systematic review of the evidence of their effectiveness was inconclusive. The aim of this pilot project was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…During the 18-month trial period, the participants' numbers dropped from 141 to 48 [16]. Another study that compared the effect of NRT in combination with EAP had 7 out of 19 participants who completed the study [4]. Several factors may have contributed to the dropout rate in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the 18-month trial period, the participants' numbers dropped from 141 to 48 [16]. Another study that compared the effect of NRT in combination with EAP had 7 out of 19 participants who completed the study [4]. Several factors may have contributed to the dropout rate in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that employed a similar EAP protocol for persistent allergic rhinitis [22, 34] and smoking cessation [4, 17] found that EAP was well tolerated by participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major inhibiting factor is nicotine withdrawal symptoms [4,5,6], including emotional distress, depressed mood, anxiety and sleep disturbances. In the USA, more than 80% of quitting efforts are unsuccessful [7].…”
Section: Introductionmentioning
confidence: 99%